2018
DOI: 10.18584/iipj.2018.9.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Promoting or Protecting Traditional Knowledges? Tensions in the Resurgence of Indigenous Food Practices on Vancouver Island

Abstract: Indigenous knowledges are increasingly promoted within scholarship and policy making as a necessary component of the well-being and self-determination among Indigenous Peoples. This article contributes to this discussion by raising practical and ethical questions surrounding the resurgence of traditional food practices in Western Canada. Based on ethnographic fieldwork conducted with cultural activists and Elders in central Vancouver Island, this article reveals how this resurgence is framed by competing and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Two of the 34 FFQ food items were excluded from the index because their classification made them culturally ambiguous: "ice cream" could refer to nontraditional store-bought brands as well as akutaq (often referred to as Alaska Native ice cream) and "donuts", which was indistinguishable between western or Alaska Native varieties. Of the remaining 32 items, 9 traditional food items were common to the local region and consumed by Alaska Native communities prior to western influences, such as wild berries, moose, whale (including whale fat / whale oil) and fish (including baked and fried salmon, fish and walrus soup) [26]. Similar foods were grouped to reduce the data, such as "baked salmon" and "fish soup" into "fish", or "sodas" and "sweetened fruit drinks" into "sweet drinks".…”
Section: Methodsmentioning
confidence: 99%
“…Two of the 34 FFQ food items were excluded from the index because their classification made them culturally ambiguous: "ice cream" could refer to nontraditional store-bought brands as well as akutaq (often referred to as Alaska Native ice cream) and "donuts", which was indistinguishable between western or Alaska Native varieties. Of the remaining 32 items, 9 traditional food items were common to the local region and consumed by Alaska Native communities prior to western influences, such as wild berries, moose, whale (including whale fat / whale oil) and fish (including baked and fried salmon, fish and walrus soup) [26]. Similar foods were grouped to reduce the data, such as "baked salmon" and "fish soup" into "fish", or "sodas" and "sweetened fruit drinks" into "sweet drinks".…”
Section: Methodsmentioning
confidence: 99%
“…It is observed that kitchen, classroom and community landscape have an important role for the exchange of knowledge about traditional practices and for strengthening the recognition of food and natural heritage. However it is learned, knowledge transmission has always played an important role in cultural survival (Muller, 2018), and is fundamental for the sustainability of native culture and habitats as part of the identity of contemporary Baja California natives (Wilken-Robertson, 2018).…”
Section: The Cultural Transmission Of Traditional Food Knowledgementioning
confidence: 99%
“…To support greater sustainability, and to reduce environmental impacts from urbanization and food production, it is crucial to focus on localizing food production and stimulating local consumption to alleviate some of the “negative impacts of neoliberal regimes” and the disadvantages of global food trade (Muller 2018, 1). Urban agriculture (UA) in its many forms (e.g., community gardens, private gardens, roof‐top growing, urban chickens) offers a way forward that affords cities with greater means to feed their citizens while promoting social and economic development and self‐sufficiency, and reducing urban food insecurity levels and environmental degradation (Walker 2016).…”
Section: Introductionmentioning
confidence: 99%